PENGARUH ARUS PENGELASAN TERHADAP KEKUATAN IMPAK DAN KEKERASAN BAJA ST.37 LAS SMAW DENGAN ELEKTRODA E7016 DAN E308 - MUCHLIS KADAFI; Nanda Pranandita; Yang Fitri Arriyani (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The quality of the welding joint is important in welding. Welding current is one of the factors that affect the quality of the connection. This study aims to determine the effect of SMAW welding current on the impact strength and hardness of ST.37 steel. The variables used in this study are the current variations of 80 A, 100 A and 125 A. The method used is experimental. Based on the impact test data, the 80 A current variation obtained an average impact energy of 193.861 Joules, while the average impact value was 2.423 Joule/mm2. With a current variation of 100 A, the average impact energy is 203.918 Joules and the average impact value is 2.548 Joule/mm2. The current variation of 125 A obtained an impact energy of 203.918 Joules and an impact value of 2,469 Joule/mm2. The 80 A current variation has the lowest average impact value and the 100 A current variation has the highest average impact value. The results of the hardness test for current variations of 80 A, 100 A, 125 A, obtained the highest average hardness value occurs at a current variation of 80 A with a value of 51.00 , while the lowest average hardness value occurs at a current variation of 125 A with a value of 50.279 . Based on the research data, it can be concluded that the variation of the welding current affects the impact strength and hardness.